PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KECERDASAN SOSIAL SISWA SMA NEGERI 5 PEKANBARU TAHUN PELAJARAN 2015/2016 - Sulaiman Syah; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect of group guidance onimprovement of social intelligence IA class XI student of SMAN 5 Pekanbaru academicyear 2015/2016. This research was conducted in SMA Negeri 5 Pekanbaru from March2016 to May 2016. The method used is a method of real-experimental with patternspretest-posttest control group design. Research subjects in this study is a class XIstudent of SMAN 5 Pekanbaru with a low level of social intelligence. Data collectioninstrument was a questionnaire using Likert scale is modified. Data analysis techniqueused is the technique of nonparametric statistical correlation. Based on the results ofWilcoxon test is apparently a difference of social intelligence level of students beforeand after the implementation of the guidance of the group amounted to 38.2%.Furthermore, after the comparison between the experimental group and the controlgroup by Mann-Whitney test results there are significant differences of socialintelligence level of students in the experimental group with the level of socialintelligence of students in the control group.Keywords: Guidance Group, Social Intelligence